Effectiveness Evaluation of the Student Research Proposal Presentation Program at Scientific Writing Course - Kasmanah, Kasmanah; Suseno, Muchlas; Setiadi, Samsi (LADU: Journal of Languages and Education, 2024)
Higher education increasingly emphasizes the importance of developing students' academic and professional abilities, including scientific communication and presentation skills. The research proposal presentation program is a strategic initiative in responding to these needs, but challenges in its implementation still exist. Evaluate the effectiveness of student research proposal presentation programs in the Scientific Writing course at UNINDRA and identify strengths and weaknesses in the delivery of material and student argumentation structure. Evaluative research involves collecting data from the results of presentation evaluations, feedback from lecturers or other participants, and assessing the quality of presentations. Qualitative and quantitative data analysis techniques were used, with thematic analysis techniques to identify patterns or themes in participant feedback and evaluation. The evaluation showed that the research proposal presentation program provided significant benefits for lecturers and students. However, there are challenges in the learning process due to inadequate support in CPMK and material distribution. The high lecturer-student ratio also hinders the implementation of the ideal presentation. Internal obstacles such as lack of courage and suboptimal preparation of presentation materials also affect the quality of presentations. The need for adjustments in the preparation of the curriculum and teaching methods, including aligning the CPMK with the CPL and ensuring that the plan for the presentation of research proposals is included in the RPS. It is necessary to provide adequate time and improvement of presentation equipment to improve the quality of presentation and feedback. Better integration between CPMK and CPL will create a globally competitive generation of academics and professionals. Thus, this program can be more effective in achieving higher education goals in developing students' academic and professional abilities.